Pharmaceutical research in Wilhelmine Germany: the case of E. Merck - Carsten Burhop (Max Planck Institute for Research on Collective Goods, 2008)
In this paper, we describe the emergence and evolution of pharmaceutical research at the German company E. Merck during the late 19th and early 20th century. Revolutionary changes in the scientific knowledge base, especially the rise of bacteriological research, and the market entry of dyestuff producers into pharmaceuticals made the re-organisation of pharmaceutical research during the 1890s a necessary corporate strategy. Consequently, Merck restructured its in-house research between 1895 and 1898. Moreover, the firm deepened its co-operation with universities and other outside inventors. Jointly and severally, the firm depended on outside inventors for the generation of new products, whereas in-house scientists improved the productive efficiency. Moreover, we show that a significant number of new products were launched between the late 1890s and 1905. During the following years, however, resource constraints restricted Merck's innovative capacity.
Keywords: N83; O32; 610; Business history; pharmaceutical research; case study; Pharmazeutische Forschung; Reorganisation; Business History; Deutschland (bis 1945)